If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -3 = 9(x + -1) Reorder the terms: -3 + 9x = 9(x + -1) Reorder the terms: -3 + 9x = 9(-1 + x) -3 + 9x = (-1 * 9 + x * 9) -3 + 9x = (-9 + 9x) Add '-9x' to each side of the equation. -3 + 9x + -9x = -9 + 9x + -9x Combine like terms: 9x + -9x = 0 -3 + 0 = -9 + 9x + -9x -3 = -9 + 9x + -9x Combine like terms: 9x + -9x = 0 -3 = -9 + 0 -3 = -9 Solving -3 = -9 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 8(2x+4)-7(2x+3)=51 | | 6.4/m=2 | | 59/6 | | 4(5x-(3-5y+4x)+4y)= | | X-6.6=4.1 | | 5d-6=-21 | | 65x+2=90 | | (x^2+10x-5)=0 | | 3(f-12)=-12 | | 18c^2=6c+0 | | 0.09x+5=22 | | 18c^2z=6c+0 | | 2*c=6.4 | | -3(x+5)=18 | | (a^-3/3b)^4 | | 6(-2x+1)=-54 | | X+6.6=4.1 | | 3(f-2)=-12 | | x^3/4y^-1/4/x^1/2y^-1/2 | | 16/3/x^1/3 | | x/3=2.6 | | 5/9(f-32)=62.1 | | 0.09x+5=29 | | 38.4=6v | | 18.75*m=3 | | -6(5x-8)=-282 | | 9.09x+5=22 | | x+12=22x | | 7.5x=90 | | 6(5x-8)=-282 | | 18.75/m=3 | | 7x+2x-131=130 |